EXAMINING CUSTOMER CONTENTMENT WITH INDOMARET POINTKU APPLICATION SERVICES THROUGH E-SERVQUAL - Kalbuana, Nawang (Journal of Data Analytics, Information, and Computer Science, 2024)
A digital software program called Indomaret Poinku offers a unique shopping experience in addition to a number of other services. A number of helpful features are available on Indomaret Poinku to facilitate the purchase pro2ss at affordable costs. This research's issue is that the system frequently encounters errors. Numerous user evaluations of the program may be found on the Google Play Store. Users rated the Indomaret Poinku application with 4.3 stars. Users reply with both favorable and negative comments. The E-ServQual approach is employed in this study to assess Indomaret Poinku's service quality and identify the discrepancy between expected and actual services. According to the study's findings, Indomaret Pointku's service quality is inadequate because, according to the computation findings, Q is insufficient or Q>1, and the resultant value of 0.97 indicates that it is not possible to declare that the services provided by Indomaret Poinku are of high quality.  Keywords: Service Quality, E-ServQual, CRM